Serum protein and electrolyte imbalances are associated with chemotherapy induced neutropenia. Issue 7 (July 2022) - Abbasi, Benazir; Hayat, Amjad; Lyons, Mark; Gupta, Ananya; Gupta, Sanjeev
Abstract: Introduction: Cancer and its treatment using various chemotherapeutic agents can have many adverse side effects. These side effects often result in significant changes in haematological and biochemical composition of blood. As a result, the regular monitoring of serum biochemical and haematological changes plays an important role in management of disease. The present study aimed to determine the relationship between haematological and biochemical changes in neutropenic cancer patients following chemotherapy. Specifically we evaluated the association between neutrophil count and serum proteins and electrolytes. Methods: For this purpose we analysed retrospectively collected laboratory results from two independent patient cohorts. Each cohort was divided into a control group consisting of patients with normal haematological parameters and a study group which included patients with reduced neutrophil counts. Neutropenic patients (study group) were cancer patients on chemotherapy. Results and conclusion: Blood samples of cancer patients in study group showed reduction in haemoglobin, neutrophils and platelets. Neutropenic group showed a significant reduction in serum albumin, total protein, calcium, and potassium. Our results show that patients with severe neutropenia had pronounced changes in serum protein and electrolytes and increased incidence of abnormal serum protein and electrolyte level. The changes in the neutrophil counts showed a positive correlation with the changes in serum protein and electrolyte levels. A similar trend was seen in both the patient cohorts: the discovery set (176 patients) and the validation set (200 patients). Taken together our results suggest that chemotherapy-induced neutropenia is associated with dysregulation in haemoglobin, platelets, serum proteins and electrolytes. Abstract : Chemotherapy; Serum Albumin; Serum total Protein; Serum Calcium; Serum Potassium; Neutropenia.